الدولة الاتحادية دراسة تحليلية مقارنة في الأشكال والقواعد والمميزات والعيوب (Sirte University Journal of Humanities, 2022)
In today's world، man has known four forms of the federated state ، and these forms of federation are  Personal union، Confederation (independent)، Real or actual union، and Federal union، which progress on the scale of the strength of the bond - according to the previous arrangement - from the weakest to the strongest، where the Federal union is the strongest of those bonds in this form of states، as the study showed.The study aims to clarify those forms and pinpoint their advantages and disadvantages. It also attempts to understand the best form of the federal state among those forms in terms of (a) the predominance of advantages over disadvantages، and (b) in terms of the suitability of this form for the developing world in general and for the countries of our Arab nation in particular.The study concluded that the federal form of the state best fits the developing world، especially in our Arab societies، due to the multiple advantages offered by this form، mainly mitigating the risk of emergence of dictatorships، equitable allocation of power and wealth، which leads to the establishment of a democratic regime with equitable citizenship in which people of all groups، genders، and ethnicities enjoy equal rights and are subject to fair laws in various duties.Overall، the federal form of the state empowers people in any society adopting it to enjoy the material and moral wealth of their country. It also becomes a catalyst in the transition of such society from backwardness، chaos and instability to more secure، stable and social satisfaction
Keywords: federal state; personal union; confederation; actual or real union; federation